Prehospital notification for major trauma patients requiring emergency hospital transport: A systematic review. Issue 3 (31st August 2017) - Synnot, Anneliese; Karlsson, Adrian; Brichko, Lisa; Chee, Melissa; Fitzgerald, Mark; Misra, Mahesh C; Howard, Teresa; Mathew, Joseph; Rotter, Thomas; Fiander, Michelle; Gruen, Russell L; Gupta, Amit; et al.
Abstract: Objective: This systematic review aimed to determine the effect of prehospital notification systems for major trauma patients on overall (<30 days) and early (<24 hours) mortality, hospital reception, and trauma team presence (or equivalent) on arrival, time to critical interventions, and length of hospital stay. Methods: Experimental and observational studies of prehospital notification compared with no notification or another type of notification in major trauma patients requiring emergency transport were included. Risk of bias was assessed using the Cochrane ACROBAT‐NRSI tool. A narrative synthesis was conducted and evidence quality rated using the GRADE criteria. Results: Three observational studies of 72, 423 major trauma patients were included. All were conducted in high‐income countries in hospitals with established trauma services, with two studies undertaking retrospective analysis of registry data. Two studies reported overall mortality, one demonstrating a reduction in mortality; (adjusted odds ratio (OR) 0.61, 95% confidence interval (CI) 0.39 to 0.94, 72, 073 participants); and the other demonstrating a nonsignificant change (OR 0.61, 95% CI 0.23 to 1.64, 81 participants). The quality of this evidence was rated as very low. Conclusion: Limited research on the topic constrains conclusive evidence on the effect of prehospital notification on patient‐centered outcomes after severe trauma. Composite interventions that combine prehospital notification with effective actions on arrival to hospital such as trauma bay availability, trauma team presence, and early access to definitive management may provide more robust evidence towards benefits of early interventions during trauma reception and resuscitation.